Islam as a Reaction to Exclusion: The ReDiscovery of Muslim Identity Among Arab Immigrants’ Descendants in Marseille - la Forgia, Enrico Maria (Italian Sociological Review, 2025)
For many “Beurs” - a slang word referring to French citizens who are descendants of Arab immigrants - (Sayad, 1994), Islam is a marker of identity (Ballard, 2018). Since they are often identified through negative stereotypes by French whites, the construction of Muslim identities might be understood as a coping mechanism against racism: Islam can provide a positive identity. In this frame, Sayad’s approach could enlighten the re-discovery of Muslim identity among Arabs’ descendants. In fact, despite “Beurs” are not proper immigrants, they seem to experience a double absence (Sayad, 1999). On one hand, their Frenchness is questioned by white French, on the other, they are physically absent from their grandfathers’ homeland. Hence, for many of them, the myth of the return does not entail a physical movement to the ancestral countries but a re-discovery of Islam as the main feature of their personality and community. The paper analyses some of the patterns of identity retrenchment enacted by “Beurs”. We ask: How does this identity-retrenchment take form? Which actors are involved? How is it connected to the exclusion operated by the French State? The research, conducted in Marseille between 2019-2020, draws on 33 interviews with “Beurs” and key informants (heads of cultural/religious associations) and considers the analysed identity retrenchment as intertwining with the ethnic-based exclusion enacted by the French State - that imposes a hierarchical ethnic classification of the national population (Avallone, 2018) -, and as a reaction to a modern continuum of Sayad’s double absence: Their trajectories are hence more understandable.